PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PADA PT TRIO ESTRO CASUAR DI KOTA BATAM - Julianto, Leonard; Nainggolan, Nora Pitri (SCIENTIA JOURNAL, 2021)
This research is intended to know the effect of product quality and trust on customer loyalty at PT Trio Estro Casuar. The method of analysis used in this study were quantitative analysis and obtained questionnaires for data used. The customer of PT Trio Estro Casuar were the population for this research, of which is 125 customers. The technique used for sampling is the Non-Probability sampling technique which uses saturated sampIing with a sample of 125 customers of PT Trio Estro Casuar. Furthermore, the collected data were analyzed using muItiple linear regression analysis and hypothesis testing to determine the effect of product quality and trust on customer loyalty at PT Trio Estro Casuar using the SPSS (Statistical Package for the Social Sciences) calculation tool version 25. The resuIts of this study indicate that Product quality and trust have a positive and significant effect on customer loyalty at PT Trio Estro Casuar. Product quality variable partially has a positive and significant effect on the customer Ioyalty variable and the trust variable partially has a positive and significant effect on the customer Ioyalty variable. SimultaneousIy, product quality and trust have a positive and significant effect on customer IoyaIty at PT Trio Estro Casuar.